2021
DOI: 10.1080/19371918.2021.1877589
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of COVID-19 Fear, Well-Being and Life Satisfaction in Turkish Society

Abstract: This study aims to examine the relationship between the fear of COVID-19, well-being, and life satisfaction perceptions of people aged 18 and over living in Turkey. Another aim of the study is to reveal whether the participants' COVID-19 fear, well-being, and life satisfaction perceptions change according to various socio-demographic characteristics. In the study, data was collected from 3111 people through a questionnaire created via Google Form on the internet. The data collection process was carried out on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 39 publications
11
59
2
5
Order By: Relevance
“…In studies conducted in Poland, Uchmanowicz et al ( 2019 ) observed moderate to high life satisfaction in more than three-quarters of nurses and midwives, while Piotrkowska et al ( 2019 ) found that oncology nurses reported an average level of life satisfaction. Compared to our findings, higher levels of life satisfaction during the COVID-19 pandemic were also observed among self-quarantined Chinese people (Li et al, 2021 ), the general population of Poland (Trzebiński et al, 2020 ), the general population of Turkey (Özmen et al, 2021 ), and uninfected adults in China (Zhang et al, 2020b ). During the COVID-19 pandemic, healthcare professionals have had to deal with heavy workloads, limited resources, and the risk of exposure to the virus; therefore, it has been stated that healthcare institutions should support their employees to reduce their concerns (Zhang et al, 2020a ).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In studies conducted in Poland, Uchmanowicz et al ( 2019 ) observed moderate to high life satisfaction in more than three-quarters of nurses and midwives, while Piotrkowska et al ( 2019 ) found that oncology nurses reported an average level of life satisfaction. Compared to our findings, higher levels of life satisfaction during the COVID-19 pandemic were also observed among self-quarantined Chinese people (Li et al, 2021 ), the general population of Poland (Trzebiński et al, 2020 ), the general population of Turkey (Özmen et al, 2021 ), and uninfected adults in China (Zhang et al, 2020b ). During the COVID-19 pandemic, healthcare professionals have had to deal with heavy workloads, limited resources, and the risk of exposure to the virus; therefore, it has been stated that healthcare institutions should support their employees to reduce their concerns (Zhang et al, 2020a ).…”
Section: Discussioncontrasting
confidence: 57%
“…Our second model showed that the frequency of thinking about death and the fear of caring for COVID-19 patients also affected life satisfaction, explaining 16% of the variance in life satisfaction (Table 5 ). Özmen et al ( 2021 ) reported that life satisfaction was lower among participants who feared COVID-19 ( β = − 0.115, t = − 6.448; p < 0.001), while Bozdağ and Ergün ( 2020 ) reported in their study on nurses and physicians that those who were worried about being infected with COVID-19 had lower psychological resilience ( β = − 0.20; p < 0.01).…”
Section: Discussionmentioning
confidence: 97%
“…The results of this study are similar to the studies revealing that the fear of COVID-19 is higher in women [52][53][54]. Studies conducted on Turkish participants revealed that both in healthy normal population and athlete population, women had greater fear and anxiety for COVID-19 scales than men [38,43,[55][56][57][58]. The fact that women are more affected by psychological distress such as depression, anxiety, adjustment disorder, perceived stress, post-traumatic stress disorder and insomnia caused by COVID-19 can be explained by the fact that women are more psychologically vulnerable [59][60][61].…”
Section: Discussionsupporting
confidence: 89%
“…On the one hand, fear is one of the main factors involved in PTSD symptoms [ 114 , 115 ], even during the COVID-19 pandemic situation [ 116 ] and, specifically, fear of COVID-19 can be associated with a wide range of mental health problems, such as anxiety, traumatic stress, and distress [ 117 ]. On the other hand, the literature on the relationship between fear of COVID-19 and well-being shows conflicting data: fear of COVID-19 has not been shown to have a direct link with quality of life [ 118 ], but in other studies it predicts lower levels of well-being [ 119 ].…”
Section: Discussionmentioning
confidence: 99%